Increased histone citrullination in juvenile idiopathic arthritis - Parackova, Zuzana; Zentsova, Irena; Malcova, Hana; Cebecauerova, Dita; Sediva, Anna; Horvath, Rudolf (Frontiers in Medicine, 2022)
Objective Posttranslational modifications (PTMs) of proteins are crucial for regulating various biological processes. However, protein alteration via PTMs, and consequently, the creation of new epitopes, can induce abnormal autoimmune responses in predisposed individuals. Immunopathogenesis of several rheumatic diseases, including the most common childhood form, juvenile idiopathic arthritis (JIA), is associated with the generation of autoantibodies against such modified proteins. Dysregulated generation of neutrophil extracellular traps (NETs) can be a source of post-translationally altered proteins. Thus, we investigated the role of PTMs and the presence of NET-associated markers in JIA patients. Methods We recruited 30 pediatric patients with JIA (20 with active disease and 10 in remission) and 30 healthy donors. The serum concentrations of citrullinated histone H3 (citH3), peptidyl arginine deiminases (PADs), and NET-related products were detected using ELISA, and the number of citH3+ neutrophils was assessed using flow cytometry. Results The serum levels of citH3 and PADs were higher in active as well as in remission JIA patients than in healthy donors. Similarly, the number of citH3+ neutrophils was higher in the peripheral blood of patients with JIA, implying an enhanced process of NETosis. This was effectively reflected by elevated serum levels of NET-associated products, such as neutrophil elastase, LL37, and cell-free DNA-histone complexes. Additionally, 16.7% of active JIA patients were seropositive for carbamylated autoantibodies, the levels of which declined sharply after initiation of anti-TNFα therapy. Conclusion Collectively, our data suggest that the accelerated process of NETosis and PTMs in JIA may result in the generation of anti-citrullinated/carbamylated autoantibodies against various epitopes later in life, which could be prevented by effectively regulating inflammation using immune therapy.